EFFECT OF CARBENECILLIN AND CEFOTAXIME ON CALLUS INDUCTION AND DEVELOPMENT SOMATIC EMBRYOS OF MALAYSIAN INDICA RICE MR219 - Rahman, Zuraida Ab; Othman, Ayu Nazreena; Amir Amran, Amirah Balqis; Arifah Basiron, Nur Najwa; Abu Bakar, Norliza; Seman, Zulkifli Ahmad (International Journal of Research -GRANTHAALAYAH, 2022)
Carbenicillin and cefotaxime, two antibiotics routinely employed to exclude Agrobacterium tumefaciens during plant transformation, were studied for their effects on callus growth and the formation of somatic embryos. Antibiotics were tested to see how they responded to the regeneration of Malaysian indica rice cv. MR219. In a preliminary study, callus fresh weight gain appeared to be improved in media containing 200 mg/L carbenicillin and 300-400 mg/L cefotaxime but was severely hindered in media containing higher concentrations. Somatic embryos were discovered in greater numbers in the medium containing 200 mgl-1 carbenicillin or 300 mgl-1 cefotaxime, at 76 and 71, respectively. It was possible that these antibiotics showed a positive response on somatic embryos development when compared to those without antibiotics. Carbenicillin and cefotaxime concentrations greater than 300 mg/L should not be utilized for the process